Pengaruh Terapi Relaksasi Autogenik terhadap Kualitas Tidur Lansia - Herdarna, Alida Reka; Untari, Rita (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: The Elderly are the final stage of a life phase that will experience gradual changes in both physical, psychological, and social aspects. As they age, the elderly often experience problems with their sleep. The decline in the quality of sleep in the elderly will have a negative impact on health, characterized by the presence of physiological and psychological balance disorders. Autogenic relaxation therapy is a non-pharmacological therapy that comes from within oneself in the form of words and thoughts that make the body feel calm and peaceful, so that it can overcome sleep problems that occur in the elderly. Objectives: This study aims to determine the effect of autogenic relaxation therapy by listening to classical music on the quality of sleep of the elderly in the Gunung Sinogo Ngargorejo Ngemplak Boyolali. Methods: This study used a quantitative research design. This type of research is a pre-experimental study with a one-group pretest-posttest design. The sampling technique used was purposive sampling with a sample size of 21 people. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Data normality was tested using the Shapiro-Wilk test and hypothesis testing using the paired sample t-test. Results: The research sample was dominated by elderly people aged 60-74 years (elderly) (71.4%), female gender (76.2%), samples who were not in school (71.4%), samples who were not working (71.4%), and samples who lived with their families (57.1%). The p-value was 0.000 (p-value <0.05), meaning that there was an effect of autogenic relaxation therapy by listening to classical music on the quality of sleep of the elderly. Conclusion: Autogenic relaxation therapy using classical music has an impact on the sleep quality of elderly people in Gunung Sinogo, Ngargorejo, Ngemplak, Boyolali Keywords: Autogenic relaxation therapy, Sleep quality, Elderly